Differential Relationships of Reactive Astrocytes and Microglia to Fibrillar Amyloid Deposits in Alzheimer Disease - Serrano-Pozo, Alberto (2013)
While it is clear that astrocytes and microglia cluster around dense-core amyloid plaques in Alzheimer disease (AD), whether they are primarily attracted to amyloid deposits or are just reacting to plaque-associated neuritic damage remains elusive. We postulate that astrocytes and microglia may differentially respond to fibrillar amyloid β (Aβ). Therefore, we quantified the size distribution of dense-core Thioflavin-S (ThioS)-positive plaques in the temporal neocortex of 40 AD patients and the microglial and astrocyte responses in their vicinity (≤50 μm), and performed correlations between both measures. As expected, both astrocytes and microglia were clearly spatially associated with ThioS-positive plaques (p = 0.0001, ≤50 μm vs. >50 μm from their edge), but their relationship to ThioS-positive plaque size differed; larger ThioS-positive plaques were associated with more surrounding activated microglia (p = 0.0026), but this effect was not observed with reactive astrocytes. Microglial response to dense-core plaques appears to be proportional to their size, which we postulate reflects a chemotactic effect of Aβ. By contrast, plaque-associated astrocytic response does not correlate with plaque size and seems to parallel the behavior of plaque-associated neuritic damage.